Le Maroc francophone en classe du FLE en Pologne : état des lieux et proposition didactique .......... 179 (Pensées orientale et occidentale : influences et complémentarité II, 2021)
FRENCH-SPEAKING MOROCCO IN FRENCH AS A FOREIGN LANGUAGE CLASS IN POLANDThe article contains an idea for a lesson of French as a foreign language and focuses on the reading of a fragment from the Moroccan writer Tahar Ben Jelloun’s novel Enfant de sable. In the theoretical part, the author of the text analyses modern conceptions of interculturality in a language class as well as the place of literature in teaching foreign languages. The author also analyses the presence of Moroccan culture in French classes in Poland and the reasons why this presence seems so scarce. The objectives of the proposed lesson target communication skills (reading comprehension, oral interaction) and socio-cultural goals (getting to know a Moroccan author writing in French and increased awareness of cultural specificity of a foreign society). The chosen fragment illustrates a problem that is culturally distant to a Polish learner (a father broken by the fact that his seven children are all female, then apparently rejoicing at the birth of a boy). The proposed lesson develops as follows: it opens by an introductive discussion about Morocco and a short presentation of the author; the main part consists of reading the chosen fragment and completing some text-related exercises; finally, there follows a discussion aimed at achieving more cultural distance, focused on two questions: what elements of the fragment should be modified if the novel was to take place in Poland (and remain realistic) and what the learners’ emotions are toward the protagonist. Carrying out the lesson plan in one of Cracow’s high schools proved that the learners were able to achieve the present goals, and seemed genuinely interested in the discussed novel.